2001
DOI: 10.1046/j.1472-8206.2001.00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of xenobiotics by amine oxidases

Abstract: Although the cytochrome P450 (CYP) system ranks first in terms of catalytic versatility and the wide range of xenobiotics it detoxifies or activates to reactive intermediates, the contribution of amine oxidases and in particular of monoamine oxidases (MAOs) to the metabolism of xenobiotics is far from negligible but has been largely neglected. In this review on the involvement of amine oxidases in the metabolism of xenobiotics, the major characteristics reported for the CYP system (protein, reaction, tissue di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…The resulting hydroxypiperaquine would undergo spontaneous cleavage into an aldehyde and an amine molecule, which could be further oxidized to the carboxylic acid. Although P450 is the most common metabolizing enzyme system of xenobiotics, the contribution of MAO is significant in the oxidative N-dealkylation of primary, secondary, and tertiary amines (Benedetti, 2001). A similar metabolic pattern, as proposed for PQ, can be seen for citalopram where an aldehyde is formed from the tertiary amine by MAO and further oxidized to the corresponding carboxylic acid by aldehyde oxidase (Rochat et al, 1998).…”
Section: Human Urinary Metabolites Of the Antimalarial Piperaquinementioning
confidence: 64%
“…The resulting hydroxypiperaquine would undergo spontaneous cleavage into an aldehyde and an amine molecule, which could be further oxidized to the carboxylic acid. Although P450 is the most common metabolizing enzyme system of xenobiotics, the contribution of MAO is significant in the oxidative N-dealkylation of primary, secondary, and tertiary amines (Benedetti, 2001). A similar metabolic pattern, as proposed for PQ, can be seen for citalopram where an aldehyde is formed from the tertiary amine by MAO and further oxidized to the corresponding carboxylic acid by aldehyde oxidase (Rochat et al, 1998).…”
Section: Human Urinary Metabolites Of the Antimalarial Piperaquinementioning
confidence: 64%
“…MAO is responsible for the metabolism of dopamine and other aminecontaining neurotransmitters (Rutledge and Jonason, 1967). MAO is also involved in the metabolism of xenobiotics (pollutants and pharmaceuticals) (Benedetti, 2001). The present study showed a positive relationship between MAO activity and PFAS across brain regions in all of the tested correlations, which may indicate xenobiotic induced stress and concurrent elevated activity of protective enzymes.…”
Section: Discussionmentioning
confidence: 85%
“…The bioactive amines present in food represent a health hazard when consumed in large amount if the natural mechanism for their catabolism is impaired by disease or pharmacological agents or if the individual is genetically deficient [23,30]. Under normal conditions, amines ingested through foods are quickly metabolized by conjugation or by oxidation reactions by amine oxidase enzymes such as monoamine oxidase (MAO), diamine oxidase (DAO), polyamine oxidases (PAO) and N-methyl transferase [21,[31][32][33]. Individuals with respiratory and coronary heart diseases, hypertension problems or vitamin B12 deficiency are at risk because they are sensitive to smaller amounts of amines [4,5,34].…”
Section: Physiological and Toxicological Aspectsmentioning
confidence: 99%